Dangerous Intercourse : Gender and Interracial Relations in the American Colonial Philippines, 1898-1946 - Winkelmann, Tessa, 1981- (Book collections on Project MUSE., 2022)
"Dangerous Intercourse details the history of a variety of interracial relationships between Americans and the Filipino, Indigenous, Moro, Spanish and other residents of the Philippines during the period of formal United States colonial rule, 1898-1946, highlighting what such relations meant for both the U.S. empire and the individuals involved"--